Caracterização da criação de abelhas como subsídio para políticas públicas voltadas ao desenvolvimento da meliponicultura e apicultura em Araçoiaba da Serra, Estado de São Paulo - Manrique, Allas Henrique Haro (Universidade Federal de São Carlos, 2025)
Considering the importance of bees in their ecosystem services, it is understood that a fundamental process for the conservation of the biodiversity of these insects is rational breeding in line with public policies that subsidize breeders with different realities. To this end, recognizing the actors involved in the activity and their other characteristics is essential to know which paths to follow. In this sense, we sought to characterize local meliponiculture and beekeeping, aiming to identify the profile and aspects of bee breeding in the city of Araçoiaba da Serra, state of São Paulo, in order to support public policies that promote the development of the activity, based on bee conservation. To obtain the data, a semi-structured online questionnaire was used in the Google Forms® tool, widely disseminated digitally, and answered in person, obtaining 35 respondent breeders. The responses obtained were organized, tabulated, and analyzed using Microsoft Excel software, seeking qualitative and quantitative analysis. Jamovi software was used for statistical analysis between variables. It was identified that meliponiculture practitioners have independent activities, seeking help from their neighbors, while beekeepers are organized into a regional cooperative and need local instruments that contribute to better conditions for selling their products. The activity is practiced mainly for conservation and as a hobby, without technical support for improvements in management. This study contributed to obtaining data on the characterization of bee farming in the municipality of Araçoiaba da Serra, in the state of São Paulo, so that public authorities can recognize the actors involved in the activity and thus establish public environmental policies focused on the topic.
Characterization of bee breeding as a subsidy for public policies aimed at the development of meliponiculture and beekeeping in Araçoiaba da Serra, State of São Paulo
Keywords: Diagnóstico participativo; Plano municipal; Ciência-cidadã; Participatory diagnosis; municipal plan; citizen science; CIENCIAS BIOLOGICAS; 11. Cidades e Comunidades Sustentáveis; 15. Vida Terrestre